Peran Komunikasi Efektif dalam Kehidupan Sehari-hari - I Gusti Agung Satria; Rieka Yulita Widaswara; Sayu Kadek Jelantik (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Effective communication is a fundamental aspect of human life that plays an important role in building harmonious interpersonal relationships, both in the family, education, and organizational environments. This study aims to analyze the role of effective communication in everyday life, analyze the benefits of effective communication in everyday life, the application of effective communication in the family, school and campus or organizational environment so as to determine the impact of effective communication in various environments based on theory and previous research results. Through the literature study method, it was found that effective communication not only involves delivering clear messages, but also listening with empathy and creating a shared understanding. The benefits of effective communication include misunderstandings that occur when communicating, increasing cooperation in various activities, and achieving common goals. The application of good communication in various contexts, such as family, campus, and society, shows a significant positive impact on the quality of relationships, life satisfaction, and productivity. Therefore, developing effective communication skills is an important investment to achieve personal and professional goals.